SOI rate gyro sensor for automotive control - Nonomura, Y.; Fujiyoshi, M.; Omura, Y.; Fujitsuka, N.; Mizuno, K.; Tsukada, K. (Sensors and actuators. A. Physical., 2006)
A silicon on insulator (SOI) rate gyro sensor has been developed for automotive controls. The sensor detects yaw rate of automobiles. The sensor has a new open beam structure (OBS). Excitation and detection electrodes of the OBS are open toward exterior bonding pads in a plane. The FEM analysis results showed the OBS was superior to other structures. The OBS has high independency between excitation and detection modes. This good feature contributed to the stability of vibration mode for the sensor. The sensor was fabricated by the surface micro machining process to miniaturize the size. The measured characteristics show the OBS is suitable for rate gyro sensor to be small, highly precise, and low cost.